Efficiency test, 3-phase, engine type, Westinghouse alternator - Conwell, Hermon H.; Kahl, Grover Cleveland; Lindsey, Fred R.; Stauffer, Maurice I. (My University, 1907)
Introduction: An alternator is a machine, having a field and an armature, which generates an alternating current. The field may be either stationary or revolving, though usually of the revolving type. Nearly all the alternators of the present time are of the revolving field and stationary armature type, as it avoids the collection of high tension currents through brushes, since the armature may be permanently connected up, and only low tension direct -current need be fed through the rings to the field. Other advantages are, increased room for armature insulation, and, in polyphasers, the necessity for only two instead of three or more slip-rings. The revolving armature is still used to some extent on small machines of low voltage capacity. The alternaing current is produced by passing a coil of wire first over a north pole and then over a south pole, so that a current is first generated in one direction and then in the other, in the inductors. The current changes direction in the coil every time that it passes under a pole of the opposite polarity. At a point between the two poles, in passing from one to the other, the coil passes for a very small increment of time over a space in which there are no lines of force being cut and at the same time there is no current or E.M.F. generatedin the coil. At this point the E.M.F. generated is of minimum value or zero; but as soon as the coil begins to enter the field of the next pole, the E.M.F.begins to increase in the opposite direction until the point under the center of the pole piece or field of greatest density is reached, when the E.M.F. reaches its maximum value and again begins to decrease to zero, after which it again rises and falls in the opposite direction. When a current…
Citation: Conwell, Hermon H., Kahl, Grover Cleveland, Lindsey, Fred R., and Stauffer, Maurice I. Efficiency test, 3-phase, engine type, Westinghouse alternator. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Alternators; Engine Testing; Electric and Magnetic Field; Theses